2016
DOI: 10.3989/ic.16.053
|View full text |Cite
|
Sign up to set email alerts
|

La incidencia de la calificación energética sobre los valores residenciales: un análisis para el mercado plurifamiliar en Barcelona

Abstract: La incidencia de la calificación energética sobre los valores residenciales: un análisis para el mercado plurifamiliar en Barcelona RESUMENEste artículo estudia de forma pionera en España la incidencia de la calificación energética sobre los valores residenciales. Para ello se analizan, mediante un modelo hedónico, datos de precios de venta de la Barcelona metropolitana. Los resultados sugieren que pasar de una calificación G a una A incrementa el valor en un 5,11 %, equivalente de media a 16,07 euros/m 2 /es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 16 publications
8
29
0
7
Order By: Relevance
“…Similarly, the "brown discount" for a home rated as class "F" or "G" (in relation to "D") is significantly larger (−10.60%) than another one on the rental market (−3.20%). The larger impact of green labels on sales prices in relation to rental prices is a finding that had already been reported by previous work based on other certification schemes [14]. The work of Stanley et al [15] carried out in Dublin found a large price gap between best and worst houses in terms of energy performance.…”
Section: Brief Literature Review and Issues Around The Epbd Spanish Isupporting
confidence: 64%
See 1 more Smart Citation
“…Similarly, the "brown discount" for a home rated as class "F" or "G" (in relation to "D") is significantly larger (−10.60%) than another one on the rental market (−3.20%). The larger impact of green labels on sales prices in relation to rental prices is a finding that had already been reported by previous work based on other certification schemes [14]. The work of Stanley et al [15] carried out in Dublin found a large price gap between best and worst houses in terms of energy performance.…”
Section: Brief Literature Review and Issues Around The Epbd Spanish Isupporting
confidence: 64%
“…The hedonic agenda of EPC ratings has also been researched in Spain. The pioneering work of Marmolejo [14] based on listing prices in the Metropolitan Area of Barcelona found a price gap equivalent to 5.11% for A/G homes if it is assumed that the EPC ladder is perceived as a continuous scale of energy performance; or 9.62% under the hypothesis that market agents assume that EPC ratings are a nominal measure of energy efficiency. In a further paper, Marmolejo & Chen [3] for the same city reported a price premium of 7.8% for the A/G gap.…”
Section: Brief Literature Review and Issues Around The Epbd Spanish Imentioning
confidence: 99%
“…For example, the pioneering research of Dinan and Miranowsky [52] revealed that improvements in energy efficiency applied in the real-estate market in Des Moines, Iowa, equaled a reduction in energy consumption of 1 USD (while maintaining the house at a comfortable temperature of 18 • C), which represented a market premium of 11.63 USD in price. In recent years, subsequent studies have addressed the impact of energy labelling on real-estate prices, such as the Energy Star certification [53][54][55][56], the LEED (Leadership in Energy and Environmental Design) scheme [55,56], the Energy Performance Certificates (EPC's) from the European Energy Performance of Buildings Directive [57][58][59][60][61][62][63][64], and others schemes [65], by identifying different levels in the market premiums associated with better-ranked homes. For example, the study by Bio Intelligence Service [66]-commissioned for the purpose of assessing the European Directive-reveals that the effect of each of the EPC label levels (expressed in letters) on the price ranges from 0.4% in Oxford to 11% in Vienna; it is 4.3% in Marseille, 3.2% in Lille and 2.9% in Brussels.…”
Section: The Configuration Of Real Estate Pricesmentioning
confidence: 99%
“…Como resultado, se establece una etiqueta -que formalmente es muy similar al certificado energético aplicado por la Directiva Europea de Eficiencia Energética en las Edificaciones (Official Journal of the European Union, 2003) -y con un ranking en letras que va desde la "A" a la "G, ordenadas de más a menos eficiente y siendo la "E" la que representa el estándar constructivo contenido en la reglamentación térmica vigente. Para obtenerla, se estableció un mecanismo, que la mayoría de las veces hace uso de un procedimiento simplificado por medio de un cálculo Fuerst et al, 2013Gelegenis et al, 2014;Marmolejo, 2016), u otros (Fuerst y Shimizu, 2016), identificando distintos niveles en la formación de los markets premium asociados a las viviendas mejor calificadas. En esa lógica, los desarrolladores inmobiliarios han generado sus productos en base a estos atributos, generando la internalización de los atributos urbanos y estableciendo productos diferenciados según su ubicación espacial.…”
Section: Promoción De La Eficiencia Energética Y Sustentabilidad De Vunclassified